2005
DOI: 10.1016/j.clpt.2004.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Paroxetine, a cytochrome P450 2D6 inhibitor, diminishes the stereoselective -demethylation and reduces the hypoalgesic effect of tramadol

Abstract: It is concluded that paroxetine at a dosage of 20 mg once daily for 3 consecutive days significantly inhibits the metabolism of tramadol to its active metabolite M1 and reduces but does not abolish the hypoalgesic effect of tramadol in human experimental pain models, particularly in opioid-sensitive tests.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
58
0
2

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 95 publications
(64 citation statements)
references
References 39 publications
4
58
0
2
Order By: Relevance
“…[8][9][10] Additionally, similar to our results in rats (Table 3), these human studies have shown that the AUCs of the M1 metabolites after single oral doses of T are nonstereoselective. 8,10 This was also true for steady-state data after multiple oral dosing of an immediate release formulation of T. 8 On the other hand, another study 13 investigating the pharmacokinetics of the enantiomers of T and M1 after multiple oral doses of a sustained release formulation of rac-T demonstrated stereoselectivity in the plasma concentrations of M1 in favor of the (À)-enantiomer [(À):(þ) plasma concentration ratios of 1.15 to 1.40]. Our data in rats suggest a stereoselective metabolism of T in the GI tract in favor of the (À)-enantiomer.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…[8][9][10] Additionally, similar to our results in rats (Table 3), these human studies have shown that the AUCs of the M1 metabolites after single oral doses of T are nonstereoselective. 8,10 This was also true for steady-state data after multiple oral dosing of an immediate release formulation of T. 8 On the other hand, another study 13 investigating the pharmacokinetics of the enantiomers of T and M1 after multiple oral doses of a sustained release formulation of rac-T demonstrated stereoselectivity in the plasma concentrations of M1 in favor of the (À)-enantiomer [(À):(þ) plasma concentration ratios of 1.15 to 1.40]. Our data in rats suggest a stereoselective metabolism of T in the GI tract in favor of the (À)-enantiomer.…”
Section: Discussionsupporting
confidence: 90%
“…8,10,14,15 A very recent study 8 indicated that, whereas the area under the plasma concentration-time curves (AUCs) of M1 enantiomers were similar in extensive metabolizers, very little (þ)-M1 was generated in poor metabolizers. Overall, these studies indicate that the pharmacokinetics and pharmacodynamics of T are both stereoselective and complex, and their understanding in different patient populations and disease states requires measurement of the individual enantiomers of T and its active metabolite M1.…”
Section: Introductionmentioning
confidence: 97%
“…Although in that article the authors identified both racemic T and racemic M1 as active components, an interaction pd model combining the effects of T and M1 could not be established. T is still a matter of active research, for example, it has been suggested as a new probe for cytochrome P450 2D6 phenotyping (11) and in a recent study (12), the analgesic effects of T were decreased after coadministration of paroxetine (a cytochrome P450 2D6 inhibitor) confirming again that M1 is an important element of T activity (13). To date a mechanistic pk/pd model addressing the different contribution of the enantiomers of T and the active metabolite M1 has not been established yet.…”
Section: Introductionmentioning
confidence: 99%
“…Parts of this work were previously presented as a poster as follows: Germain JM, Patroneva A, Connolly SM, Fatato P, Paul J, Isler JA, Burczynski M, GuicoPabia C, and Nichols AI (2007) An assessment of drug-drug interactions: the effects of desvenlafaxine succinate and duloxetine on the pharmacokinetics of the CYP2D6 probe desipramine in healthy subjects. , 1997;Laugesen et al, 2005), the antiarrhythmic amiodarone (Fukumoto et al, 2006), the analgesic codeine (Zanger et al, 2004), and the cyclooxygenase-2 inhibitor celecoxib (Werner et al, 2003). It is important, therefore, that physicians are aware of the potential for clinically relevant interactions when prescribing antidepressants.…”
mentioning
confidence: 99%
“…For example, paroxetine and fluoxetine strongly inhibit CYP2D6 (K i of 2.0 and 3.0 M, respectively), whereas citalopram and sertraline have been shown to be moderate or weak inhibitors (K i of 19 and 22.7 M, respectively) (Skjelbo and Brosen, 1992;von Moltke et al, 1995;Preskorn, 2003;Preskorn et al, 2007a). CYP2D6 is responsible for the metabolism of drugs (and activation of prodrugs) commonly used to treat various medical conditions; some examples include the antiestrogen tamoxifen (Stearns et al, 2003), the atypical opioid tram-adol (Mason and Blackburn, 1997;Laugesen et al, 2005), the antiarrhythmic amiodarone (Fukumoto et al, 2006), the analgesic codeine (Zanger et al, 2004), and the cyclooxygenase-2 inhibitor celecoxib (Werner et al, 2003). It is important, therefore, that physicians are aware of the potential for clinically relevant interactions when prescribing antidepressants.…”
mentioning
confidence: 99%